Study on seismic performance of prefabricated self-centering beam to column rotation friction energy dissipation connection. (15th August 2021) - Yun, Chen; Chao, Chen; Cong, Chen
Abstract: Under severe earthquakes, a significant number of unexpected plastic hinges and brittle failure were found in conventional rigid beam to column welded connections of steel frames. To improve the seismic performance of steel frames, an innovative prefabricated self-centering beam to column (SCBC) connection was proposed and experimentally validated in this paper. The SCBC connection consisted of disc springs at the bottom flange of beam and a rotation friction hinge (RFH) at the beam end. The bottom disc springs could not contact with slab systems and provided restoring moment, whereas the RFH was designed to dissipate seismic energy. Firstly, its configuration form and design methodology were introduced. Then cyclic tests of a 1/4 scale SCBC connection specimen was carried out and the responses of the SCBC connection was compared to that of the RFH. Finally, the restoring force model of the SCBC connection was established through theoretical analysis. The experimental and analytical results demonstrated full flag-shaped hysteretic curves of the SCBC connection under cyclic loadings, verifying the desirable energy dissipation capacity and reliable self-centering capability of the SCBC connection. The calculation results based on the restoring force model were in good agreement with the test results, showing that the proposed restoring force model could reasonably predict the hysteretic behavior of the SCBC connection.